Biological and clinical significance of BRCA2 - Michalak, Małgorzata; Filip, Agata; Karczmarek-Borowska, Bożenna; Wojcierowski, Jacek; Zmorzyński, Szymon (Contemporary Oncology/Współczesna Onkologia, 2011)
Nowadays, diagnostics enables detection of cancer-related mutations. It concerns germline mutations as well as de novo mutations. The number of genetics tests available for specific tumors increase incessantly. BRCA1 and BRCA2 are high-penetrant genes, but still their functions and mechanisms leading to cancer caused by their mutations remain unknown. Germline alterations in BRCA1 and BRCA2 sequences are related to hereditary breast cancer syndrome (HBC), hereditary breast and ovarian cancer syndrome (HBOC), hereditary ovarian cancer syndrome (HOC). Primary and secondary tumors prevention and choice of the best treatment are the benefits of the detection of BRCA2 mutations. Research on correlation between the tumor phenotype and the type of mutation is continuously performed. This research may have an impact on the development of more effective drugs.